2003
DOI: 10.1007/s00198-002-1370-3
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and compliance with risedronate in clinical practice

Abstract: The purpose of this study was to determine compliance with dosing instructions, and the prevalence of possible adverse events, when risedronate is used in clinical practice. 219 patients were studied. We found that despite counseling one in four patients were non-compliant with dosing instructions. Those patients who did not stay upright after taking risedronate were more likely to have an adverse event and to discontinue the drug. Adverse events were experienced by 38% of patients, the commonest being gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 10 publications
1
49
0
6
Order By: Relevance
“…Although several studies show low persistence, in the order of 20-50%, many studies show persistence rates that are rather similar to those reported in randomised controlled trials. In particular, those from the UK show rates on the order of 80% [18,22,24,25]. The lowest rates reported are from North America where in some studies, low persistence may reflect the lack of an affordable treatment for some patients, known to be an important factor in non-persistence.…”
Section: Pattern Of Adherencementioning
confidence: 99%
“…Although several studies show low persistence, in the order of 20-50%, many studies show persistence rates that are rather similar to those reported in randomised controlled trials. In particular, those from the UK show rates on the order of 80% [18,22,24,25]. The lowest rates reported are from North America where in some studies, low persistence may reflect the lack of an affordable treatment for some patients, known to be an important factor in non-persistence.…”
Section: Pattern Of Adherencementioning
confidence: 99%
“…терапии способствовал увеличению числа больных, продол-жавших (не прекративших) лечение БФ в течение года и бо-лее по сравнению с ежедневным приемом [22][23][24][25][26][27][28].…”
Section: бфunclassified
“…Bisphosphonates are mostly related to esophageal irritation and ulceration with rarer reports of esophageal perforation or upper gastrointestinal bleeding. Patients complain of heartburn, nausea, and upper abdominal or chest pain (32). Although frequently related to bisphosphonate use, in prospective, randomized, placebo-controlled clinical trials with oral bisphosphonates, there were no significant differences in GI side effects between patients treated with oral bisphosphonates or placebo.…”
Section: Bisphosphonates -Side Effectsmentioning
confidence: 99%
“…Most patients reporting GI intolerance to bisphosphonates are able to continue on the same drug (33); however, Hamilton and cols. (32) demonstrated that 76% of the patients who discontinued the use of risedronate did so because of gastrointestinal side effects (32). No differences in the incidence of gastrointestinal side effects between daily and weekly or monthly dosing groups in clinical trials were observed (34).…”
Section: Bisphosphonates -Side Effectsmentioning
confidence: 99%